The Fundamentals of taxation - De Leon, Hector S. (Manila : Rex Book Store, 1974)
Taxes are truly the lifeblood of the nation as without funds the government cannot fulfill its varied functions - nay, cannot continue to exist. It is therefore, important that the people are made aware of their obligation to pay taxes willingly and promptly.
Chapter I : General principles -- Chapter II : National taxation -- Chapter III : Tax administration and procedure -- Chapter IV : Local taxation
Keywords: TAXATION -- LAW AND LEGISLATION; TAXATION -- LAW AND LEGISLATION -- PHILIPPINES